Omega-3 Fatty Acids as an Adjunct Therapy in Sepsis: Insights and Implications: A Narrative Review - Swati; Madhvi Awasthi; Nameet Jerath (Journal of Clinical and Diagnostic Research)
Sepsis is a severe condition that affects a vast number of people globally, irrespective of their underlying health status. Sepsis arises from a disproportionate immune response to infection, leading to life-threatening organ dysfunction. This dysfunction is assessed using scoring systems like the Sequential Organ Failure Assessment (SOFA), where a score increase of two points or more signifies a high mortality risk in infected patients. Despite advances in critical care, mortality rates remain high, emphasising the need for novel therapeutic strategies. Inflammation, marked by mitochondrial dysfunction, oxidative stress and cytokine release, is central to sepsis, causing cellular damage and organ failure. Omega-3 Fatty Acids (FAs), Polyunsaturated Fatty Acids (PUFAs) essential for human health, have emerged as potential candidates due to their anti-inflammatory and immunomodulatory properties. Omega-3 FAs can positively influence SOFA scores. The mechanisms underlying the therapeutic effects of omega-3 FAs in sepsis are complex and multifaceted. These FAs may exert their beneficial effects by modulating the inflammatory response, attenuating oxidative stress, improving endothelial function. Neurological outcomes, such as improved Glasgow Coma Scale (GCS) scores, have also been reported. Importantly, it is associated with shorter hospital stays and reduced time on Mechanical Ventilation (MV). In conclusion, omega-3 FAs appear to be promising adjunct therapy for sepsis. While further research is needed to fully elucidate their mechanisms of action and to establish optimal dosing strategies, the available evidence suggests that these FAs may improve outcomes in patients with sepsis.